Critical Fluid Injection Volumes for Uncontrolled Fracture Ascent. Issue 14 (14th July 2020) - Davis, Timothy; Rivalta, Eleonora; Dahm, Torsten
Abstract: Hydrofracturing is a routine industrial technique whose safety depends on fractures remaining confined within the target rock volume. Both observations and theoretical models show that, if the fluid volume is larger than a critical value, pockets of fluid can propagate large distances in the Earth's crust in a self‐sustained, uncontrolled manner. Existing models for such critical volumes are unsatisfactory; most are two‐dimensional and depend on poorly constrained parameters (typically the fracture length). Here we derive both analytically and numerically in three‐dimensional scale‐independent critical volumes as a function of only rock and fluid properties. We apply our model to gas, water, and magma injections in laboratory, industrial, and natural settings, showing that our critical volumes are consistent with observations and can be used as conservative estimates. We discuss competing mechanisms promoting fracture arrest, whose quantitative study could help to assess more comprehensively the safety of hydrofracturing operations. Plain Language Summary: Fractures in rocks can act as channels for fluids. Fracking, or hydrofracturing, involves injection of fluids at high pressure in order to grow fractures within the rock and increase its permeability. Fluid volumes need to be kept below a threshold value: If the fluid volume is larger, then the stresses at the tips of the fluid pocket will be large enough for the fluids to force their way around by fracturing the rock ahead of them. Previous theoretical models for the critical volumes are unsatisfactory as they are two‐dimensional and based on poorly constrained parameters. We derive and test a new three‐dimensional equation that uses only rock and fluid parameters. We find that typical volumes injected in hydrofracturing operations are over the limit we define. We argue they are still mostly safe as additional processes often hinder fracture growth. Further work is needed to comprehensively quantify mechanisms that hinder hydrofracture arrest. Key Points: We define critical volumes for fractures under the influence of a stress gradients that cause self‐sustaining propagation We define such critical volumes analytically such that they are independent of scale. These are verified numerically The equation predicts the correct scale in natural and analog examples but for hydro‐fracturing its too low